AN ANALYSIS OF COHESION IN DESCRIPTIVE TEXT OF ENGLISH TEXTBOOK USED IN TENTH GRADE OF SMA MUHAMMADIYAH 8 KISARAN - Dina Putrika Tanjung; Tiarnita Maria Sarjani br Siregar (Universitas Negeri Medan, 2022)
This study focused on finding out the cohesiveness and finding out the dominant types of cohesion of descriptive in English textbook used in the tenth grade students of SMA Muhammadiyah 8. In this study, the researcher used qualitative research design. In this study, the source of data is the descriptive text found in English textbook entitled “Bahasa Inggris” for grade X Senior High School published by Ministry of Education and Culture of Indonesia, 2017 written by Utamiwidiati, Zuliati Rohmah, and Furaidah.This study was conducted by finding out the coheviness and finding out the dominant types of cohesion of descriptive in English textbook used in the tenth grade students according to Miles &Huberman and Saldana (1994) technique. Miles &Huberman and Saldana elaborate several steps of analyzing data; they are data collection, data reduction, data display, and data verification/conclusion. The technique of collecting data of this study were collected through reading attentively and accurately the Textbook Entitled “Bahasa Inggris” for Grade X published by Ministry of Education and Culture of Indonesia from certain pages that have been chosen by the researcher as the samples. From the data, the researcher discovered 93 cohesions. From the 93 cohesions, the researcher reduced the data which contained only the grammatical and lexical cohesions. In finding out the dominant cohesion, the researcher discovered that the grammatical cohesion dominantly is conjunction. Meanwhile, for the lexical cohesion is collocation dominantly.Keywords: cohesion, descriptive text, English textbook